2015
DOI: 10.1042/bj20150420
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-binding module assisting glycosynthase-catalysed polymerizations

Abstract: Carbohydrate-binding modules (CBMs) are found within multi-modular polysaccharide degrading enzymes [glycoside hydrolases (GHs)]. CBMs play a critical role in the recognition of plant cell-wall polysaccharides and enhance the hydrolase activity of their cognate catalytic domains by increasing enzyme substrate proximity. Mimicking their role in Nature, we, in the present study, propose that CBMs may assist in vitro glycosynthase-catalysed polymerization reactions to produce artificial polysaccharides. Glycosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This could explain why gene annotation/classification of these enzymes based on sequence similarities and protein folds often results in the significant overlap between the two enzyme classes (Hidaka et al, 2004; Lombard et al, 2014; Roston, Wang, Kuhn, & Benning, 2014). However, few studies have explored the role of CBMs on transglycosylation activity of GHs and none have so far explored the possibility of the reaction mechanism directly employing CBMs (Codera, Gilbert, Faijes, & Planas, 2015; Mizutani et al, 2012; Stockinger et al, 2015). While CBMs or lectin‐like domains have been never reported previously to directly participate in the catalytic reaction step for glycosidic bonds synthesis by GHs, these domains have been shown to play important roles in the functioning of several GTs.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why gene annotation/classification of these enzymes based on sequence similarities and protein folds often results in the significant overlap between the two enzyme classes (Hidaka et al, 2004; Lombard et al, 2014; Roston, Wang, Kuhn, & Benning, 2014). However, few studies have explored the role of CBMs on transglycosylation activity of GHs and none have so far explored the possibility of the reaction mechanism directly employing CBMs (Codera, Gilbert, Faijes, & Planas, 2015; Mizutani et al, 2012; Stockinger et al, 2015). While CBMs or lectin‐like domains have been never reported previously to directly participate in the catalytic reaction step for glycosidic bonds synthesis by GHs, these domains have been shown to play important roles in the functioning of several GTs.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why gene annotation/classification of these enzymes based on sequence similarities and protein folds often results in significant overlap between the two enzyme classes (Hidaka et al, 2004;Lombard et al, 2014;Roston et al, 2014). However, few studies have explored the role of CBMs on transglycosylation activity of GHs and none have so far explored the possibility of the reaction mechanism directly employing CBMs (Codera et al, 2015;Mizutani et al, 2012;Stockinger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The weight-average molecular weight of the products ranged from 9.5 kDa (dp 29) for (4G3G)n to 14.5 kDa (dp 30) for (4G4G3G)n to 12.9 kDa for (4G4G4G3G)n. Recently, the Planas laboratory reported that, in some cases, polymers with a slightly higher DP are obtained when a carbohydrate-binding module (CBM), recognizing the respective polymer, is added to the polymerization reaction. 42 The presence of a CBM may reduce precipitation of the higher molecular weight polysaccharides, thus promoting the temporary generation of an oversaturated solution. Similar effects were observed when a CBM was covalently attached to a glycosynthase via a short peptide linker.…”
Section: ■ Introductionmentioning
confidence: 99%